THE ACCOUNTABILITY OF SPECIAL AUTONOMY FUND MANAGEMENT AFTER THE IMPLEMENTATION OF LAW NUMBER 2 OF 2021 CONCERNING THE SECOND AMENDMENTS TO LAW NUMBER 21 OF 2001 CONCERNING SPECIAL AUTONOMY FOR THE PROVINCE OF PAPUA IN YAHUKIMO REGENCY - Nakamnanu, Kusi Hendra; Sumartono, Sumartono; Rochmah, Siti (Faculty of Administrative Science, Universitas Brawijaya, 2023)
This study aims to evaluate the value of accountability in the management of the Special Autonomy Fund in Yahukimo Regency after the implementation of Law Number 2 of 2021 as the basis for managing special autonomy funds for the next 20 years.This research was conducted using the five dimensions of Accountability according to Koppel: transparency, liability, Controllability, Responsibility, and responsiveness. They used a qualitative approach with the stages of data collection, data analysis, and report writing. The research data was obtained from the Yahukimo Regency Regional Development Planning Agency and separated into primary and secondary data. Preliminary data was obtained through observation, interviews, and documentation from several informants. Informants were determined based on their role and involvement in the Special Autonomy Fund in the Yahukimo Regency. Secondary data sources were obtained through previous research, scientific journals, written documents from related agencies, and electronic and print media. The results showed that Special Autonomy through Law Number 2 of 2021 has regulated the value of transparency and accountability in its management very well. Still, in its implementation, the importance of accountability, especially in the dimensions of liability and responsiveness, has not been optimal where the Yahukimo Regency government has not been able to guarantee all activities that have been carried out under the expectations and wishes of Indigenous Papuans (OAP). The need for management with high accountability values supported by long-term planning and competent human resources. This research was conducted because of the phenomenon of Special Autonomy for Papua Province, which has entered a new phase or Special Autonomy Fund Volume II, also driven by the problem of the implementation of the management of the Special Autonomy Fund in Yahukimo Regency, which has not been optimal, this study aims to provide recommendations for particular autonomy policies for Papua Province, especially Yahukimo Regency to improve people's welfare.